2014
DOI: 10.3390/toxins6010283
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Approach to Study Cylindrospermopsin Distribution in Tilapia (Oreochromis niloticus) under Different Exposure Conditions

Abstract: Cylindrospermopsin (CYN) is a cytotoxic cyanotoxin produced by several species of freshwater cyanobacteria (i.e., Aphanizomenon ovalisporum). CYN is a tricyclic alkaloid combined with a guanidine moiety. It is well known that CYN inhibits both protein and glutathione synthesis, and also induces genotoxicity and the alteration of different oxidative stress biomarkers. Although the liver and kidney appear to be the main target organs for this toxin based on previous studies, CYN also affects other organs. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Fish may be exposed to the toxin via several routes, including by dermal exposure through skin and gills, or by oral uptake. After entering the body, CYN accumulates in various tissues (Guzmán‐Guillén et al ., ; Kinnear, ), in fish mainly in the liver and kidneys (Guzmán‐Guillén et al ., ). As a highly water‐soluble molecule, CYN also has a high affinity for blood and lymph (Kinnear, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fish may be exposed to the toxin via several routes, including by dermal exposure through skin and gills, or by oral uptake. After entering the body, CYN accumulates in various tissues (Guzmán‐Guillén et al ., ; Kinnear, ), in fish mainly in the liver and kidneys (Guzmán‐Guillén et al ., ). As a highly water‐soluble molecule, CYN also has a high affinity for blood and lymph (Kinnear, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of studies have been conducted on the acute effects of CYN on fish. In vivo and in vitro research studies have shown that CYN toxicity might be mediated by reactive oxygen species (ROS) (Liebel et al ., 2011; Silva et al ., 2017) and, as a result, lead to alterations, in areas such as the antioxidant defence system, lipid peroxidation, protein carbonilation and DNA oxidation (Guzmán‐Guillén et al ., 2014, 2015a; Puerto et al ., 2011, 2014). In addition, it has had biological effects ( e.g ., developmental toxicity and a high mortality rate) on embryo fish ( Danio rerio ).…”
Section: Introductionmentioning
confidence: 99%
“…In O. niloticus , animals sampled at fish pounds in Egypt accumulated up to 1.5 μg g −1 of CYN in their livers 20 . For this same species, a strongest immunolocalization of CYN in the liver was detected, and the immunolabeling was intensified over time after exposure, demonstrating the biocamulation and toxicity of CYN in the liver of animals after acute and sub‐chronic CYN‐exposure 26 . For H. malabaricus , in animals exposed to a single intraperitomial injection (50 μg k −1 ) of aqueous extract of CYN‐producing cyanobacteria, on average 6.79 and 5.61 ng g −1 of CYN was detected in the liver, after 7 and 14 days of exposition, respectively 24 …”
Section: Discussionmentioning
confidence: 96%
“…Although in vivo studies evaluating the toxic effects of CYN are related to a few fish species, 21‐27 they have demonstrated a broad action of CYN in several target organs. However, there are no data about the putative genotoxicity and mutagenicity caused by CYN in different tissues from fish.…”
Section: Introductionmentioning
confidence: 99%